Penerapan penggunaan DIVA Score pada Pemasangan Intra Vena Perifer - Indah Purnama Sari (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
Intravenous access on a patient requires skilled skills. These skills must be based on knowledge of anatomy and the level of difficulty that will be faced in the process of the action. Using the DIVA scale is a way that can be used to assess whether the installation has a high level of difficulty or not.The application of the DIVA Scale at the Awal Bros Group Hospital was carried out to provide education and reference for all nurses in doing this to detect the level of difficulty before access is installed.Application of scale DIVA is useful for reducing the number of attempts required to install intravenous access. The training was carried out on January 19 2024, which was attended by 136 nurses from 9 hospitals.